Dental Students’ Perspective of Transitioning from Pre-Clinical to Clinical Practice - Jazzar A; Gadi R; Rajeh M; AlDehlawi H; Alhamed S; Badeeb T (Advances in Medical Education and Practice)
Ahoud Jazzar,1 Rawan Gadi,2 Mona Rajeh,2 Hebah AlDehlawi,1 Sana Alhamed,1 Tahani Badeeb3 1Department of Oral Diagnostic Sciences, Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi Arabia; 2Department of Dental Public Health, Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi Arabia; 3Department of Prosthodontics, Faculty of Dentistry, King Abdulaziz University, Jeddah, Saudi ArabiaCorrespondence: Ahoud Jazzar, Email ojazzar@kau.edu.saIntroduction: This study aimed to investigate how dental students at King Abdulaziz University Faculty of Dentistry transitioned from pre-clinical to clinical instruction and how this change affected their learning outcomes. Understanding this transition was crucial to identify the challenges faced by students and the support they required.Methods: A mixed-methods approach was utilized, combining qualitative insights from focus group discussions with quantitative data from surveys. Focus groups gathered detailed student experiences regarding their transition, while surveys measured workloads, anxiety levels, and perceptions of clinical competence.Results: The results showed that students have a lot of difficulties because of their heavier workloads, higher levels of anxiety, and the need for better integration of academic knowledge with practical abilities. Concerns over clinical competence and the necessity of improving communication with patients and healthcare teams are other characteristics of the transition phase. The findings highlighted how important structured support networks are for reducing transition-related stress and improving students’ readiness for clinical duties. These networks include peer mentorship, orientation programs, and customized curriculum modifications.Discussion: The study emphasized the value of early exposure to clinical settings and the inclusion of soft skill development in the curriculum, such as empathy and communication. The research advocated for comprehensive reforms in dental education, emphasizing the need for a holistic approach that addresses both the academic and emotional well-being of students. Dental faculties can contribute to the development of more competent and self-assured dental practitioners by improving support systems and incorporating practical experiences earlier in the educational timeline.Keywords: dental education, transition experiences, pre-clinical to clinical, mixed-methods approach, student challenges, support systems, curriculum design, learning outcomes, clinical competence